Optimal design of wind machine impeller for frost protection based on CFD and its field test on airflow disturbance - Wenye, Wu; Yongguang, Hu; Shuo, Yang; Kangqian, Mao; Xiaoyong, Zhu; Pingping, Li (International Journal of Agricultural and Biological Engineering, 2015)
Wind machines have been increasingly applied to prevent frost damage through airflow disturbance in tea fields and orchards. An impeller is the most important component of the machine. However, there are few studies on customized impeller design or airflow disturbance performance. The objective of this study was to design a new impeller for frost protection wind machines based on reverse engineering and CFD simulation. The characteristic parameters of an impeller include blade cross-section shape, installation angle, sweep angle, hub ratio and blade number. The optimal combination of the above parameters was obtained through the simulation of the impeller’s aerodynamic performance. Field tests were conducted in a tea field to evaluate airflow disturbance performance of the designed impeller. The result shows that at a certain rotation speed and rotation diameter, the optimal combination of impeller parameters was: single arc cross-section of ϕ2400 mm, installation angle of 15°, sweep angle of 87°, hub ratio of 0.3 and blade number of 4, of which the impeller could achieve the highest usage of 0.56, the least consumed power of 1.363 kW and more uniform distribution of surface pressure on the windward side. Compared with other commercial frost protection wind machines, the maximum airflow velocity of the developed impeller was higher at 12 m in front of it. The probability of airflow velocity above 3.0 m/s within 30 min was the highest (71.7%), indicating its improvement of airflow stability. Without swing the new impeller could cover an effective area of 300 m2, which was similar to that of the commercial ones. Keywords: frost protection, wind machine impeller, CFD, reverse engineering, airflow disturbance, tea orchard DOI: 10.3965/j.ijabe.20150805.1415 Citation: Wu W Y, Hu Y G, Yang S, Mao K Q, Zhu X Y, Li P P. Optimal design of wind machine impeller for frost protection based on CFD and its field test on airflow disturbance. Int J Agric & Biol Eng, 2015; 8(5): 43－49.